Comprehensive genotype–phenotype analysis in 230 patients with tetralogy of Fallot. Issue 5 (30th November 2009) - Rauch, Ralf; Hofbeck, Michael; Zweier, Christiane; Koch, Andreas; Zink, Stefan; Trautmann, Udo; Hoyer, Juliane; Kaulitz, Renate; Singer, Helmut; Rauch, Anita
Abstract : Background: Tetralogy of Fallot (ToF), the most frequent cyanotic congenital heart disease, is associated with a wide range of intra- and extracardiac phenotypes. In order to get further insight into genotype–phenotype correlation, a large cohort of 230 unselected patients with ToF was comprehensively investigated. Methods and results: 230 patients with ToF were studied by karyotyping, comprehensive 22q11.2 deletion testing and sequencing of TBX1, NKX2.5 and JAG1, as well as molecular karyotyping in selected patients. Pathogenic genetic aberrations were found in 42 patients (18%), with 22q11.2 deletion as the most common diagnosis (7.4%), followed by trisomy 21 (5.2%) and other chromosomal aberrations or submicroscopic copy number changes (3%). Mutations in JAG1 were detected in three patients with Alagille syndrome (1.3%), while NKX2.5 mutations were seen in two patients with non-syndromic ToF (0.9%). One patient showed a recurrent polyalanine stretch elongation within TBX1 which represents a true mutation resulting in loss of transcriptional activity due to cytoplasmatic protein aggregation. Conclusion: This study shows that 22q11.2 deletion represents the most common known cause of ToF, and that the associated cardiac phenotype is distinct for obstruction of the proximal pulmonary artery, hypoplastic central pulmonary arteries and subclavian artery anomalies. Atrioventricular septal defect associated with ToF is very suggestive of trisomy 21 and almost excludes 22q11.2 deletion. We report a further patient with a recurrent polyalanine stretch elongation within TBX1 and for the first time link TBX1 cytoplasmatic protein aggregation to congenital heart defects.